2000
DOI: 10.1074/jbc.m003794200
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase II is required for mitoxantrone to signal NFkB activation in HL60 cells

Abstract: SUMMARYTopoisomerase II is a target for a number of chemotherapeutic agents used in the treatment of cancer. Its essential physiological role in modifying the topology of DNA involves the generation of transient double-strand breaks. Anti-cancer drugs, such as mitoxantrone, which target this enzyme, interrupt its catalytic cycle and give rise to persistent double strand breaks which may be lethal to a cell. We investigated the role of such lesions in signaling the activation of the transcription factor NFκB by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The presence of topoisomerase IIα (TOP IIα) in the complex is indicative of a possible dual role for the CDC5L complex in the cell nucleus. It has been suggested that TOP IIα may be involved in transcription because of its enhanced expression during mitosis (Boland et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of topoisomerase IIα (TOP IIα) in the complex is indicative of a possible dual role for the CDC5L complex in the cell nucleus. It has been suggested that TOP IIα may be involved in transcription because of its enhanced expression during mitosis (Boland et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism for therapeutic efficacy of mitoxantrone in treatment of multiple sclerosis is that it may inhibit migration of inflammatory cells into and within the central nervous system. DNA damage resulting due to poisoning of topoisomerase II by mitoxantrone acts as a signal for NF-kappa B activation and induction of apoptosis (Boland et al 2000). Mitoxantrone is 78 % bound to plasma proteins (Scott and Figgitt 2004;Wiseman and Spencer 1997).…”
Section: Mitoxantronementioning
confidence: 99%